Quality Management System in a Haemodialysis Unit and Patient Satisfaction - Athanasia Kavalieratou; Georgia Garofyllou; Eftychia Evangelidou; Michalis Mantzanas (SciMedicine Journal, 2021)
Haemodialysis Units adopt a Quality Management System to provide quality healthcare services, to promote reliability and to increase the patients’ contentment and faith they receive the best possible care. The purpose of this study was to ascertain whether the ELOT EN ISO 9001:2015 Quality Management System, “Provision of Dialysis Services in Patients with Renal Failure”, in a Haemodialysis Unit affected the patients’ satisfaction level. The Quality Management System stipulated the use of a questionnaire containing 11 questions to measure the patients’ satisfaction. The data were collected in July 2018 during the annual audit for the continuous compliance of the Haemodialysis Unit with the quality requirements. 35 patients undergoing Chronic Haemodialysis for at least the last 6 months participated. The Quality Management System enabled the identification of the patients’ individual needs and the areas that required more attention. More specifically, 97.1% of the patients stated that the services provided had been improved and that requests such as the installation of TVs and the collaboration with a dietologist have been met. 77.1% of the patients were satisfied by the healthcare provided and 88.6% were satisfied by the staff in general. Regarding the care provided by the medical staff 74.3% of the patients were satisfied, while 54.2% found the information given for their health to be adequate. All of the patients (100%) were satisfied by the care provided by the nursing staff and almost all (97.1%) felt that the nursing staff was easy to communicate with. Only 6.1% of the patients stated that specific areas required further improvement. A Quality Management System in a Haemodialysis Unit leads to a better understanding of the patients’ individual needs, allowing for higher satisfaction. Moreover, the evidence based documentation of the quality of the services provided and the emphasis put on continuous improvement further enhances the patients’ trust.